ASSESSMENT OF NEONATAL MENINGITIS IN A UNIQUE PRESENTATION WITH SEPSIS - Jahanzeb Khan Afridi; Rahida Karim; Muhammad Idrees; Shahrukh Yar; Gul e Lala; Huma Gul (Journal of Postgraduate Medical Institute, 2023)
Objective: To assess meningitis in neonates presented with sepsis to a tertiary care hospital of the province Khyber Pakhtunkhwa. Methodology: This hospital based cross sectional study was conducted at Department of Pediatrics, Hayatabad Medical Complex, Peshawar from 24th January 2021 to 24th July 2021. The neonates were enrolled through Out Patient Department (OPD) and Emergency Department (ER) with signs and symptoms that were suggestive of sepsis. The diagnosis was confirmed using lumber puncture investigation. The extracted data was then evaluated using SPSS v.24.0 for descriptive and inferential analysis. Results: In total of 168 neonates with mean age of 13.36±9.26 days, 54.9% individuals were born full term, wherein 51.2% had decreased feed, 54.9% were lethargic, and 42.7% were hypothermic. In total, 57.3% had negative blood culture, while 52.4% were diagnosed to have meningitis. In addition, 61% of the neonates had raised Total Leukocyte Count (TLC), and 64% of the neonates had increased C-Reactive Protein (CRP) of more than 0.5mg/dl. Meningitis was found to have significant association (p<0.05) with gender, hyperthermia, decreased oral feed, lethargic condition, blood culture positivity and TLC while had an insignificant (p>0.05) relationship with hypothermia, age group and age at birth (grouped) and CRP levels. Conclusion: The study concluded that more than half of the neonates presented with suggestive signs and symptoms of sepsis were positive for meningitis. High number of neonates had increased TLC and CRP.